Investigation of the GO effect on CdS quantum dot sensitized PV-cells based on the GO-TiO2 nanocomposite photoanode: modeling using the Lambert function - Yahyaoui, N.; Mansouri, S.; Yakuphanoğlu, Fahrettin (Royal Soc Chemistry, 2025)
Titanium dioxide (TiO2) and graphene oxide-TiO2 (GO-TiO2) photoanode nanocomposite solar cells, incorporating CdS quantum dots, were analyzed. The current and power density versus voltage characteristics of the fabricated photovoltaic (PV) cells were measured under different power densities. A fourfold increase in short-circuit current density, from 0.481 mA cm-2 to 2 mA cm-2, was observed by adding 0.12 g of graphene. This increase in performance is attributed to the enhanced electrical and optical properties provided by graphene, which generates more charge carriers and increases the density of electron-hole pairs by absorbing white light. Quantum dots were also employed to improve the solar cell performance. The capacitance-frequency characteristics of the graphene-TiO2 composite photoanode, based on CdS quantum dots, were studied with graphene. The negative capacitance behavior of PV cells with graphene was investigated, revealing that graphene significantly influences these values. As a result, adding graphene enhanced the inductive behavior of the quantum dot-sensitized solar cells (QDSSCs). The electrical characteristics of the solar cells were studied, and the experimental data for current and power density versus voltage were simulated using the Lambert function to explain the effect of graphene on the inductive behavior of TiO2/CdS-based cells.
Keywords: Solar-Cells; Semiconductor Nanocrystals; Recombination; Expressions; Mechanisms; Tio2